2020–2021 Vegetable Production Handbook: Chapter 7. Cucurbit Production - Josh H Freeman; Eugene J. McAvoy; Nathan S. Boyd; Mathews Paret; Qingren Wang; Christian F. Miller; Johan Desaeger; Jawwad Qureshi; Xavier Martini; Peter J. Dittmar; Phillip B. Williams (EDIS)
This chapter covers production of cucurbits, such as cantaloupe, cucumber, squash, watermelon, and pumpkin.